Functionalized MXene ink enables environmentally stable printed electronics - Ko, Tae Yun; Ye, Heqing; Murali, G.; Lee, Seul-Yi; Park, Young Ho; Lee, Jihoon; Lee, Juyun; Yun, Dong-Jin; Gogotsi, Yury; Kim, Seon Joon; Kim, Se Hyun; Jeong, Yong Jin; et al. (Nature Publishing Group, 2024)
Establishing dependable, cost-effective electrical connections is vital for enhancing device performance and shrinking electronic circuits. MXenes, combining excellent electrical conductivity, high breakdown voltage, solution processability, and two-dimensional morphology, are promising candidates for contacts in microelectronics. However, their hydrophilic surfaces, which enable spontaneous environmental degradation and poor dispersion stability in organic solvents, have restricted certain electronic applications. Herein, electrohydrodynamic printing technique is used to fabricate fully solution-processed thin-film transistors with alkylated 3,4-dihydroxy-L-phenylalanine functionalized Ti3C2T x (AD-MXene) as source, drain, and gate electrodes. The AD-MXene has excellent dispersion stability in ethanol, which is required for electrohydrodynamic printing, and maintains high electrical conductivity. It outperformed conventional vacuum-deposited Au and Al electrodes, providing thin-film transistors with good environmental stability due to its hydrophobicity. Further, thin-film transistors are integrated into logic gates and one-transistor-one-memory cells. This work, unveiling the ligand-functionalized MXenes' potential in printed electrical contacts, promotes environmentally robust MXene-based electronics (MXetronics). Here, authors demonstrate the electrohydrodynamic printing of alkylated 3,4-dihydroxy-L-phenylalanine functionalized MXene (AD-MXene) ink. The AD-MXene outperforms vacuum-deposited Au and Al electrodes, providing thin film transistors with good environmental stability due to its hydrophobicity.